Microsoft Encarta encyclopedia deluxe 2000 (Microsoft Corp., 1999)
Includes over 40,000 articles, 16,000 photos and illustrations, video clips and 3-D animations, sound clips, World Wide Web links, monthly yearbook and web link updates, multimedia collages, panoramic, 360-degree views, article sidebars, virtual tours, interactivities, and a research organizer.